The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.31616/asj.2019.0190
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Clinical Results of C1 Laminoplasty for the Treatment of Compressive Myelopathy

Abstract: Study Design: Case series.Purpose: To evaluate the radiographic and clinical results of C1 laminoplasty without fusion.Overview of Literature: C1 laminectomy has been the standard procedure for decompression at the C1 level. However, there have been some reports of trouble cases after C1 laminectomy. C1 laminoplasty might be superior to C1 laminectomy with regard to maintaining the original C1 anatomical shape, preventing compression from the posterior soft tissue, and ensuring an adequate bonegrafting site ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…described how C1 laminoplasty performed for spinal cord compression at the C1/2 level resulted in favorable outcomes, and, therefore suggested this might be an effective alternative to CIL for patients without C1–C2 instability. [ 5 ] Shimizu et al . described a 14.2% (10 patients) incidence of C1 anterior atlas arch fractures in 70 patients who had undergone C1L without fusion.…”
Section: Discussionmentioning
confidence: 99%
“…described how C1 laminoplasty performed for spinal cord compression at the C1/2 level resulted in favorable outcomes, and, therefore suggested this might be an effective alternative to CIL for patients without C1–C2 instability. [ 5 ] Shimizu et al . described a 14.2% (10 patients) incidence of C1 anterior atlas arch fractures in 70 patients who had undergone C1L without fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the patient's osteoporosis and anterolateral rotatory angulated type IIA dens fracture fragment, we assumed that a forceful reduction of the atlantoaxial anteroinferior subluxation with kyphosis to a neutral or lordotic state could cause a high risk of fixation failure and spinal cord injury. [ 10 12 ] Notably, C2 pedicle screw fixation is biomechanically stronger than C2 lamina screw fixation. [ 4 ] However, we deemed the insertion of C2 pedicle screws technically challenging because of fractures of both pars interarticularis and the type IIA dens fracture.…”
Section: Discussionmentioning
confidence: 99%
“… 11 12 13 14 15 In addition, few reports described cervical myelopathy resulting from degenerative or hypertrophic osteoarthritis of the C1-C2 joint. 16 17 18 19 20 21 22 To our knowledge, however, no study has reported cervical myelopathy caused by long-standing neglected traumatic posterior AOD and its late sequel involving the C0-C1-C2 joints. Therefore, in this report, we present a patient with cervical myelopathy caused by long-standing neglected posterior AOD and posttraumatic osteophytes of the C0-C1-C2 joints, which was successfully treated by laminectomy of the C1 posterior arch alone without occipitocervical fusion (OCF).…”
mentioning
confidence: 99%